Electrochemical studies on the removal of cadmium by methylated xanthine bases from aqueous solution - Jabbar, Md Abdul; Sabuj, Md Riad Hossain (Bangladesh Journal of Scientific Research, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjsr.v25i1.13046 Bangladesh J. Sci. Res. 25(1): 11-22, 2012